The role of the atrium in the development of the Takotsubo Syndrome – investigation of a patient-specific atrial stem cell model. (3rd October 2022) - Brandt, C; Huebscher, D; Syed Ali, G; Maurer, W; Hasenfuss, G; Nikolaev, V O; Streckfuss-Boemeke, K
Abstract: Background and aims: The Takotsubo syndrome (TTS) is characterised by an acute left ventricular dysfunction without exhibiting signs of stenosis. TTS affects mainly the left ventricle, however, its pathophysiology comprises transient impairments in left atrium functions with a prevalence of atrial fibrillation (AF) of around 18% correlating with higher ventricular heart rhythm disorders. In this study, we aimed to prove the hypothesis that molecular and cellular arrhythmic events contribute to the development of TTS under catecholamine stress and to test if the currently clinically used β-blockers (Metoprolol) or the PDE4 activator MR-L2 are suitable for Takotsubo cardiomyopathy in vitro. Methods and results: We generated induced pluripotent stem cell-derived atrial cardiomyocytes (TTS-iPSC-aCMs) from TTS patients, confirmed atrial marker expression (MLC2a, PItX2, NR2F2), and treated them with catecholamines (Iso) to mimic TTS-phenotype. Using a cytosolic Förster resonance energy transfer (FRET) based cAMP sensor, we tested the activity of phosphodiesterases (PDEs) in TTS-iPSC-aCMs and observed that after β-AR stimulation, the strong effects of the PDE4 family in the cytosol of atrial control cells were significantly decreased in aCMs of the TTS patients. This effect was rescued after application of PDE4 activator MR-L2 and is in line with the previously described downregulation of PDE4 in human atrial myocardium of AF patients. In functional studies, Iso-induced increase in systolic Ca2+ transient amplitude was more pronounced in TTS iPSC-aCM compared to controls. These effects were rescued by both, the clinically approved β-blocker Metoprolol and by MR-L2. To analyse arrhythmic events in atrial TTS CMs, we performed confocal microscope Ca2+ measurements and demonstrated that the diastolic sarcoplasmic reticulum Ca2+ leak was increased in iPSC aCMs of TTS patients compared to control under basal conditions and after Iso-treatment. In addition, TTS patients displayed faster Ca2+ kinetics compared to control cells, already under basal conditions. These results were underlined on a molecular level by increased phospholamban phosphorylation in TTS iPSC-aCM. Subsequent treatment with Metoprolol rescued the Ca2+ kinetic parameters and the increased calcium sparks in all cell lines. Conclusion: In conclusion, we were able to draw a comprehensive picture on the role of the atrium in the development of arrhythmias in TTS. We found TTS-patient-specific differences with reduced PDE4 activity, elevated arrhythmic events and enhanced reactions to catecholamines, which could be rescued by the clinically approved drug Metoprolol and partly by the PDE4 activator MR-L2. Therefore, Metoprolol has proven to be an effective treatment option for TTS and preliminary data of MR-L2 demonstrate promising effects as a new patient-specific therapeutic target for TTS under catecholamine-stress. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): German centre for cardiovascular research